Bread Factory Layout Design using BLOCPLAN - Robecca, Julian; Santosa, Alam; Saputra, Calvin Megy; Anton, Awie (Universitas Komputer Indonesia, 2024)
The aim of this research is to design a proposed layout for bread production facilities that can minimize the moving distance and material handling costs. This study used the BLOCPLAN method as the design method. The BLOCPLAN method is a facility layout design method based on a hybrid algorithm and supported by the BLOCPLAN 90. With this method, 20 alternative layouts are obtained, then the researcher chooses 3 layouts that had the greatest proximity value. Layout 13 produced a smaller total displacement distance and material handling costs, namely 56.40 meters at the cost of 489.62 rupiah, in one transfer of raw material. The initial layout of the bakery factory had a displacement distance of 68 meters and a material handling cost of 590.28 rupiah in one transfer of raw material. For this reason, layout 13 becomes a proposed layout for use by a bread production facility. In addition, the layout of the bread production facilities and production time can also be more efficient than before.